Macro Histone Variants: Emerging Rheostats of Gastrointestinal Cancers - Giallongo, Sebastiano (Cancers (Basel), 2019)
Gastrointestinal cancers (GC) are malignancies involving the gastrointestinal (GI) tract and accessory organs of the digestive system, including the pancreas, liver, and gall bladder. GC is one of the most common cancers and contributes to more cancer-related deaths than cancers of any other system in the human body. Causative factors of GC have been consistently attributed to infections, smoking, an unhealthy diet, obesity, diabetes, and genetic factors. More recently, aberrant epigenetic regulation of gene expression has emerged as a new, fundamental pathway in GC pathogenesis. In this review, we summarize the role of the macroH2A histone family in GI cell function and malignant transformation, and highlight how this histone family may open up novel biomarkers for cancer detection, prediction, and response to treatment.